Overexpression of p53 Improves Blood Glucose Control in an Insulin Resistant Diabetic Mouse Model. Issue 7 (August 2016) - Zhang, Xuemei; Duan, Wei; Lee, Wai-Nang Paul; Zhang, Yuewei; Xiang, Fenfen; Liu, Qian; Go, Vay Liang W.; Xiao, Gary Guishan
Abstract : Objective: This paper aimed to assess the physiological effects of p53 on glucose homeostasis in vivo. Methods: A recombinant adenoviral p53 (rAd-p53) vector was administered to insulin-resistant diabetic mice. Intraperitoneal glucose tolerance test was performed in all groups of mice. Changes in fasting blood glucose, serum triglycerides, C-peptide, and insulin concentrations in treated and untreated mice were measured. Analyses of the target genes related to glucose metabolism were performed. Results: Treatment with the rAd-p53 improved glucose control in a dose- and time-dependent manner and lowered significantly the fasting blood glucose, the serum triglycerides, and improved tolerance test of glucose as compared to control. Lowered blood glucose was associated with up-regulation of genes in the glycogenesis pathways, and down-regulation of genes in the gluconeogenesis pathways in the liver. Overexpressions of GLUT2, GK, PPAR-γ, and insulin receptor precursor were also observed in the liver and the pancreas of treated animals. Conclusions: Activation of p53-mediated glucose metabolism led to insulin-like antidiabetic effect in the mouse model especially by changing hepatic insulin sensitivity in the diabetic mouse model. Abstract : Supplemental digital content is available in the text.